PENGARUH KEPEMIMPINAN, MOTIVASI, DAN PEMBERIAN INSENTIF TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KEBUDAYAAN PEMUDA DAN OLAHRAGA (DIKBUDPORA) KABUPATEN BIMA - Sugeng Widakdo; Amir Tengku Ramli; Lidwina Sri Ardiasih (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the influence of leadership, motivation and incentives on employee performance. This research was conducted in the Office Education, Culture, Youth and Sports (DIKBUDPORA) Bima Regency. The samples in this study were employees in the education, culture, youth and sports department of Bima Regency, totaling 66 people, but the researchers used a sample with the Slovin formula so as to get a sample as respondents as many as 56 employees. While the method and data analysis used is a quantitative method with multiple linear regression. Based on the results multiple linear regression analysis, the partial test (t-test) proves that leadership variable (X1) has positive and significant effect on employee performance (Y) in the DIKBUDPORA office, Bima Regency, the variable of motivation (X2) has positive and significant effect on employee performance (Y) in the DIKBUDPORA office in Bima Regency, and incentives variable also have (X3) positive and significant effect to employee performance (Y) in the DIKBUDPORA office, Bima Regency. The F test result shows that leadership (X1), motivation (X2) and incentives (X3) simultaneous effect the employee performance (Y) in the DIKBUDPORA, Bima Regency, as evidenced by a value of 0.000.